Usefulness of Examining Various Patient-Reported Outcomes in Predicting Endoscopic Mucosal Healing in Ulcerative Colitis - Moon, Jung Min; Yoon, Hyuk; Park, Jihye; Shin, Cheol Min; Park, Young Soo; Kim, Nayoung; Lee, Dong Ho; Kim, Joo Sung (Turkish Journal of Gastroenterology, 2022)
Background: Endoscopy remains the gold standard for evaluating mucosal healing in ulcerative colitis. However, given its invasiveness and high cost, it is not always possible to perform it as often. This study aimed to evaluate value of numerous patient-reported symptoms in the prediction of endoscopic mucosal healing. Methods: We prospectively conducted a cohort involving 143 patients with ulcerative colitis (men: 63.6%, median age: 40.0 years) in a tertiary teaching hospital between May 2017 and May 2020. Clinical remission was defined as resolution of rectal bleeding and normalization of stool frequency, set as basic patient-reported outcomes. The presence of additional 4 patient-reported outcomes (urgency, tenesmus, mucoid stool, and night defecation) were evaluated. Endoscopic activity was graded using the Ulcerative Colitis Endoscopic Index of Severity and endoscopic mucosal healing was defined as Ulcerative Colitis Endoscopic Index of Severity 0-1. Results: A total of 44 (30.77%) ulcerative colitis patients were categorized as achieving endoscopic mucosal healing. Across different patient-reported outcomes status in predicting endoscopic mucosal healing, clinical remission status inferred from basic patient-reported outcomes was superior to additional 4 patient-reported outcomes collectively (sensitivity/specificity: Ulcerative Colitis Endoscopic Index of Severity = 0/1, basic patient-reported outcomes 59.09%/75.76%, additional 4 patient-reported outcomes 70.45%/72.73%). Combination of basic and additional patient-reported outcomes revealed increased specificity of 83.84%. Multivariate analysis adjusted for age, sex, disease extent, and disease duration also revealed consistent results that patient-reported outcomes were independently associated to endoscopic mucosal healing (P < .001). Conclusion: Recognizing the presence of additional patient-reported outcomes may be useful in clinical practice as it is a simple and easy method that not only reflects patient’s quality of life but can also relatively better predict endoscopic mucosal healing status than basic patient-reported outcomes Cite this article as: Moon JM, Yoon H, Park J, et al. Usefulness of examining various patient-reported outcomes in predicting endoscopic mucosal healing in ulcerative colitis. Turk J Gastroenterol. 2022;33(8):682-688.